2022
DOI: 10.1039/d2gc00855f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light photocatalytic metal-free multicomponent Ugi-like chemistry

Abstract: The possibility to harness the photoactivity of isocyanides in the development of metal-free Ugi-like visible light photo-triggered multicomponent transformations has been herein reported. More in detail, Ugi-3CR, Ugi-Tetrazole-3CR, and Ugi-...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Based on the above results and previous studies, 6 b ,8 f ,12 a plausible mechanism is proposed, as shown in Scheme 6. Initially, the complexation of esters 1 with B(C 6 F 5 ) 3 resulted in Lewis adduct I .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Based on the above results and previous studies, 6 b ,8 f ,12 a plausible mechanism is proposed, as shown in Scheme 6. Initially, the complexation of esters 1 with B(C 6 F 5 ) 3 resulted in Lewis adduct I .…”
Section: Resultsmentioning
confidence: 54%
“…11 c Meanwhile, they also play a crucial role in catalysts, 11 d semiconductor materials, 11 e and agricultural chemicals. 11 f Although plenty of methods have been disclosed for rapid access to imides, 12 atom-economical methods for the preparation of imides are still rare and highly desired because the formation of amide bonds in an atom-economical manner has been identified as one of the most pressing objectives of green chemistry by a roundtable of pharmaceutical industry experts (GCIPR). 13…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after, the scope of the Ugi‐like self‐catalyzed visible light photochemical transformation was further expanded to a range of multicomponent reactions including the Ugi 3‐CR, the Ugi‐tetrazole 3‐CR, the Ugi‐Joullié 3‐CR, the synthesis of secondary imides via cleavable isocyanide, and an Ugi‐Deprotection‐Mumm transacylation (UDeM) sequence (Scheme 30). [43] After short rounds of reaction conditions optimization, a selection of both aliphatic and aromatic isocyanides 2 was reacted with diverse carboxylic acids 3 including complex structures such as ibuprofen, biotin, indomethacin, and cholic acid in acetonitrile under 30 W blue LEDs irradiation to give the desired α‐amino amides 63 in up to quantitative yields (Scheme 30a). These photocatalytic conditions were also successfully applied with cyclic tertiary amines 58 such as N ‐phenyltetrahydroisoquinoline, N ‐phenylpyrrolidine, and N ‐phenylpiperidine (Scheme 30b) while the replacement of carboxylic acids 3 in the Ugi reaction with azidotrimethylsilane 64 enabled a [3+2] cyclization leading to 1,5‐disubstituted tetrazole derivatives 65 in good to excellent yields thus further proving the mildness and the robustness of isocyanides as visible light photocatalysts (Scheme 30c).…”
Section: Self‐catalyzed Photoinduced Mcrsmentioning
confidence: 99%
“…This reaction type was the modified Ugi reaction, and it was the first reported use of MCR in lipidoids synthesis. [92][93][94][95][96][97][98][99] Notably, the ethanol used in this reaction as well as the absence of catalysts are of great help in the high-throughput screening of ionizable lipids. The top-performing lipid formulations shared a common structure, which included an unsaturated lipid tail, cyclic amine headgroups, and a dihydroimidazole linker.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%